Probability of Nutrient Adequacy from Estimated Usual Intake Among Children 9–24 Months: Results from 7 MAL-ED Sites (FS10-06-19). (13th June 2019) - Antiporta, Daniel; Ambikapathi, Ramya; Bose, Anuradha; Maciel, Bruna; Mahopo, Tjale; Patil, Crystal; Turab, Ali; Chandyo, Ram; Islam, M Munirul; Bauck, Aubrey; Olortegui, Maribel; Caulfield, Laura
Abstract: Objectives: To estimate the usual energy and micronutrient intakes of children 9–24 mo of age and evaluate the probability of adequacy of the diet in 7 MAL-ED sites. Methods: Breastfeeding was evaluated biweekly from enrolment (≤17 d old) through 24 mo; beginning at 9 mo, monthly 24-hour recalls (up to 17 recalls/child) were used to quantify intakes of complementary foods. Energy, macro- and micro-nutrient intakes were calculated using site-specific food composition tables. Based on the Morseth et al (2016) analysis of the Nepal MAL-ED site, we estimated energy and nutrient intakes from breast milk to derive total energy and nutrient intakes. For each site and 3 mo-age period, we estimated usual intakes of energy and 13 micronutrients for each child, considering age, sex, month and day of the week, then predicted the distribution of intakes by age period and site. We then compared each intake distribution to the recommended dietary allowance to derive the median probability of adequacy (MPA) and respective inter-quartile range (IQR). We evaluated iron and zinc considering bioavailability. Results: Among 1669 children, median %energy (%E) from breast milk ranged from 23–71%E at 9–12 mo, and declined to 25–40%E at 21–24 mo. Iron bioavailability was low for all sites, but many diets were of moderate bioavailability for zinc. MPA were 1 (IQR = 0) in Brazil and South Africa, except for iron and vitamin E (both), calcium (South Africa) and zinc (low bioavailable diet in South Africa). MPA for zinc increased from 9–24 mo only for children consuming a diet with moderate bioavailability. MPA increased for many nutrients from 12–24 mo as the nutrient density of complementary foods increased; however, MPA for vitamin A remained low in Bangladesh and Tanzania. In Tanzania, calcium and B12 MPA declined and IQR increased as cow's milk remained in the diets of only some children. For most sites and age groups, MPA were 0 (IQR = 0) for Vitamins D, E and iron. Conclusions: MPA increases from 12–24 mo as children consume more nutrient-dense complementary foods. Ways to increase consumption of foods containing vitamins D, E, and A, and calcium are needed, as are ways to increase bioavailability of iron and zinc. Funding Sources: The MAL-ED study was supported by the Bill & Melinda Gates Foundation, through grants to the Foundation for the NIH and NIH/FIC.